Nexus between financial development, agriculture raw material exports, trade openness and economic growth of Pakistan - Muhammad Zaheer Khan; Abdul Salam Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The objective of this of the study is to evaluate the role of financial development, Agriculture raw materials and the extent of openness to trade in economic development of Pakistan for the period 1980-2012, by using Vector Auto Regressive (VAR) model. Empirical results showed that there exist a long-run relationship between financial development, agriculture raw material exports, and output growth. Normalized cointegrating equations revealed that, Raw material exports, trade openness and domestic credit to private sector are positively effecting the Economic growth of Pakistan, while M2 has negative impact on Economic growth of Pakistan. A two way causal relationship has been determined between trade openness and economic growth and raw material exports and economic growth. Our results revealed that raw material exports and finial development are positively related to agriculture growth; however, the impact of financial development is relatively week.
Keywords: 330; trade openness; agriculture raw material; exports; economic growth; vector auto regressive